2017
DOI: 10.4103/cs.cs_16_101
|View full text |Cite
|
Sign up to set email alerts
|

Getting ready for REDD+: Recognition and Donor-country Project Development Dynamics in Central Africa

Abstract: forest cover in developing countries by offering results-based payments. The international framework and agreements to allow the functioning of this mechanism are being negotiated under the United Nations Framework Convention on Climate Change (UNFCCC). The REDD+ framework adopted by the UNFCCC requires each country to fulfil specific steps to be eligible for "result-based" funds/payments, and has a phased approach: readiness (including capacity building and stakeholder consultation), implementation of demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Conservation project development can be dominated by the rules and values of international actors, as was the case of a World Bank funded REDD+ project in Central Africa (Walters & Ece, 2017).…”
Section: What Is Power and How Is It Conceptualized In Social Science...mentioning
confidence: 99%
See 1 more Smart Citation
“…Conservation project development can be dominated by the rules and values of international actors, as was the case of a World Bank funded REDD+ project in Central Africa (Walters & Ece, 2017).…”
Section: What Is Power and How Is It Conceptualized In Social Science...mentioning
confidence: 99%
“…Actor-centered power Conservation project development can be dominated by the rules and values of international actors, as was the case of a World Bank funded REDD+ project in Central Africa (Walters & Ece, 2017). Rietig (2016) shows how some NGOs have strong lobbying power and set agendas for international climate change decisions and policies.…”
Section: Localmentioning
confidence: 99%
“…The key findings of the case studies, described here, ranged from higher-scale to more-local interventions. Walters and Ece (2017) examined the dynamics of decision-making and representation in carbon forestry at international and sub-regional scales, by focusing on REDD+ project negotiations in the Congo Basin region; Mbeche (2017) and Nuesiri (2017) explored national REDD+ Preparedness Programs in Uganda and Nigeria. Ece ( 2017) examined midlevel elected sub-national government's role in in community forestry projects in Senegal.…”
Section: Key Findings and Representation Outcomes Of Case Studiesmentioning
confidence: 99%
“…In the RFGI studies described here, however, we found that while these ministries represent 'nations' in the international arena, their domestic practices (in REDD+ and in community forestry) fall grossly short of even supporting democratic principles in local decision making. While Walters and Ece (2017) do not directly address choice and recognition of local institutions, their study provides background on the international context in which multi-lateral forestry programs and their national components unfold. Mbeche (2017) and Nuesiri (2017) researched representation in REDD+ Preparedness Programs (R-PP) that support REDD+ policy design in Uganda and Nigeria (also see Marfo 2015).…”
Section: Key Findings and Representation Outcomes Of Case Studiesmentioning
confidence: 99%